The acute care of the elderly unit: providing rapid specialised care for frail older people. (2019) - Imam, Towhid; Goldsby-West, Robert; Hashemi, Nima; Earnshaw, Alan; Bramble, Joanne; Rehman, Joe; Tan, Wallace
No abstract available